2000
DOI: 10.1046/j.1365-4362.2000.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination in cutaneous leishmaniasis due to Leishmania major in different ethnic groups in Saudi Arabia

Abstract: The potential for dissemination due to cutaneous leishmaniasis was significantly higher in the nonindigenous population than in the indigenous population in Saudi Arabia. Disseminative lesions must be clinically differentiated from other skin diseases and appropriately treated by avoiding the use of intralesional drugs or physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
4
17
1
Order By: Relevance
“…Similar observations have been recorded in the past. 5,[14][15][16] In 3 of these patients, L infantum, L tropica, and L donovani were identified in individual cases. In the patient with diffuse induration of the face, the causative species was L tropica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been recorded in the past. 5,[14][15][16] In 3 of these patients, L infantum, L tropica, and L donovani were identified in individual cases. In the patient with diffuse induration of the face, the causative species was L tropica.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe this feature in our previous studies from this region, but it has been reported in other studies. 14,15,17 It may suggest a hemolymphatic dissemination of the protozoan infection from the initial lesion as a result of local factors. 17 Clinical features were almost similar irrespective of the causative Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…Three Phlebotomus species were recognized, constituting potential vector of leishmaniasis; the most probable ones were: Phlebotomus papatasi, the main human biting species, recognized main vector of Leishmania major (rural CL) (Al-Qurashi et al 2000), followed by P. sergenti, recognized vector of L. tropica (urban CL) (Al-Zahrani et al 1988). Phlebotomus papatasi (Scopoli), an endophilic species, constitute 91% of all flies caught intra-domiciliary.…”
Section: Discussionmentioning
confidence: 99%
“…"Oriental sore" was reported by Manson to occur in Arabia as far back as 1898, although at that time the cause of the condition was unknown (Manson 1898). CL is known to occur throughout the Kingdom of Saudi Arabia and is endemic in many areas, including the Western Province Peters and Al-Zahrani 1987;Al-Zahrani et al 1988;Al-Qurashi et al 2000;Al-Tawfiq and AbuKhamsin 2004), where the vector of the disease (Phlebotomus) and the natural hosts, the desert rodents (e.g., Meriones libycus and M. crassus) are present .…”
Section: Introductionmentioning
confidence: 99%
“…9 In another, smaller study, 16 of 73 (22%) patients with CL had disseminated disease. 10 Involvement of lymph nodes in patients with CL has also been described in 10% of 643 patients. 11 Other studies have described different aspects of the disease in a non-immune population.…”
mentioning
confidence: 99%